The “sapiens asteroid”. Some reflections about the Sixth Extinction (Nóema, 2015)
The paper offers a scientific-phylosophical reflection on the ecological relations among living beings, evaluated in the framework of Darwinian evolutionism. Starting with the fact of extinction as a recurrent factor in the history of life, we point out the possible human role in the massive loss of biodiversity we can observe at present time. Then we try to introduce the basis for a behavioural change which would allow us to stop this process. Our argument is centred on the crucial concept of dependence as primary condition of life: as a result, we can reach a new idea about the identity of a living being, intended in a specific ecological value. This innovative concept of identity may represent, for human beings, the starting point for the development of a more conscious behaviour, both on moral and ecological perspective.
Keywords: adaptation; biodiversity; Darwin; dependence; ecosystem; evolution; extinction; identity; relation; struggle